The Democratic People's Republic of Korea, Procedural Rhetoric and the Military-Entertainment Complex: Two Case Studies from the War on Terror. (June 2020) - Spokes, Matthew
This article explores how the Democratic People's Republic of North Korea is represented in video games developed and played during the height of the War on Terror. Drawing on Šisler's article, 'Digital Arabs: Representation in video games' (2008) and Robinson's articles 'Videogames, persuasion and the War on Terror: Escaping or embedding the military-entertainment complex? (2012) and 'Have you won the war on terror? Military videogames and the state of American exceptionalism' (2015), this article explores two case studies Tom Clancy's Splinter Cell: Chaos Theory (2005) and Tom Clancy's Ghost Recon 2 (2004) using Bogost's (2008, 2010) concept of 'procedural rhetoric' to unpack and detail the visual signifiers and gameplay mechanics of these titles in comparison with other work on games set in 'Axis of Evil' countries. The article concludes by situating the games within the military-entertainment complex more broadly (here focusing on film), arguing that North Korea is ultimately framed paradoxically in video games, a country that is viewed on the one hand as a threat to world peace and on the other as an absurdist dictatorship.